Analisis Penerapan Kurikulum Merdeka dalam Membentuk Profil Pelajar Pancasila Siswa Kelas IV SD Negeri 1205 Silenjeng - Nurhalimah Harahap; Juli Asnita Hasibuan; Era Mutiah (Dirosah Islamiyah, 2026)
This study aims to analyze the implementation of the Independent Curriculum in shaping the Pancasila Student Profile and describe its implementation and evaluation among fourth-grade students at SD Negeri 1205 Silenjeng. This study used a field approach with data collection techniques through observation, interviews, and documentation. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results indicate that the implementation of the Independent Curriculum was carried out through the planning, implementation, and evaluation stages of the Pancasila Student Profile Strengthening Project (P5). In the planning stage, the school formed a coordination team and determined the project's theme, dimensions, time allocation, model, and implementation strategy. The implementation stage was carried out through the development of a project module containing objectives, tools and materials, and activity steps. The project, implemented in the even semester, involved making piggy banks from used cans over five meetings, encompassing self-awareness activities, group formation, conceptual understanding, and product-making practices. Evaluation was conducted through observation and the use of monitoring instruments to assess program implementation and achievement of the Pancasila Student Profile dimensions. Despite challenges in managing the implementation time, this project had a positive impact on students, particularly in fostering respect for differences, social openness, and creativity.